2020
DOI: 10.1101/2020.04.20.051581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boceprevir, GC-376, and calpain inhibitors II, XII inhibit SARS-CoV-2 viral replication by targeting the viral main protease

Abstract: A novel coronavirus SARS-CoV-2, also called novel coronavirus 2019 , started to circulate among humans around December 2019, and it is now widespread as a global pandemic.The disease caused by SARS-CoV-2 virus is called COVID-19, which is highly contagious and has an overall mortality rate of 6.4% as of April 15, 2020. There is no vaccine or antiviral available for SARS-CoV-2. In this study, we report our discovery of inhibitors targeting the SARS-CoV-2 main protease (M pro ). Using the FRET-based enzymatic as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 52 publications
5
70
0
Order By: Relevance
“…Mechanistically, we found unexpected complexity in the inhibition of SARS-CoV-2 replication by simeprevir -it does not inhibit the SARS-CoV-2 viral proteins PL pro or RdRP at physiologically feasible concentrations. Simeprevir is a weak inhibitor of M pro at ~10 μM, in keeping with the IC50 at ~13.7 μM as determined in a parallel study (31). This potency of M pro inhibition unlikely accounts for the strong suppression of SARS-CoV-2 viral replication observed.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Mechanistically, we found unexpected complexity in the inhibition of SARS-CoV-2 replication by simeprevir -it does not inhibit the SARS-CoV-2 viral proteins PL pro or RdRP at physiologically feasible concentrations. Simeprevir is a weak inhibitor of M pro at ~10 μM, in keeping with the IC50 at ~13.7 μM as determined in a parallel study (31). This potency of M pro inhibition unlikely accounts for the strong suppression of SARS-CoV-2 viral replication observed.…”
Section: Discussionsupporting
confidence: 71%
“…The inhibition assay was based on fluorescence resonance energy transfer (FRET) using a fluorescent-protein-based substrate previously developed for SARS-CoV M pro (30,38). 0.1 μM of purified SARS-CoV-2 M pro was pre-incubated with 0 -250 μM simeprevir in 20 mM HEPES pH 6.5, 120 mM NaCl, 0.4 mM EDTA, 4 mM DTT for 30 min before the reaction was initiated by addition of 10 μM protein substrate (31). Protease activity was followed at 25 °C by FRET with excitation and emission wavelengths of 430 nm and 530 nm, respectively, using a multi-plate reader as described (30,38).…”
Section: In Vitro M Pro Inhibition Assaymentioning
confidence: 99%
“…Our previous study showed that when GC376 binds to the SARS-CoV-2 M pro , the covalent thioketal adduct can adapt both the S-and R-configuration. 11 The MD simulations showed that the complexes formed with GC376 in either the S-or R-configuration did not deviate from the starting structures, which is the X-ray structure, with an RMSD in protein and ligand positions from the X-ray structure smaller than c.a. 2 Å for the protein and c.a.…”
Section: Sars-mentioning
confidence: 86%
“…5B), suggesting a binding ratio of one drug per monomer, which is consistent with its mechanism of action revealed by X-ray crystallography. 11 The addition of 4 mM DTT shifted the equilibrium to one ligand per dimer (Fig. 5C).…”
Section: Sars-mentioning
confidence: 92%
See 1 more Smart Citation